Impact of tetraplegia vs. paraplegia on venoarteriolar, myogenic and maximal cutaneous vasodilation responses of the microvasculature: Implications for cardiovascular disease. (2nd January 2022) - Trbovich, Michelle; Wu, Yubo; Koek, Wouter; Zhao, Joan; Kellogg, Dean
Abstract : Objective: Cardiovascular disease (CVD) is a leading cause of mortality in persons with SCI. While macro vascular remodeling and function after SCI is well documented, changes in the micro vascular structure and function are comparably understudied, but importantly predict CVD risk. Specifically, the integrity of venoarteriolar (VAR), myogenic (MYO) and maximal vasodilation responses are largely unknown after SCI, especially in persons with tetraplegia (TP) at highest risk of CVD. This is the first to examine the differences in VAR (cuff inflation), MYO (limb dependency) and maximal vasodilation responses of the microvasculature between able bodied (AB) versus those with TP and paraplegia (PP). Design: Observational. Setting: Laboratory. Participants: Eight AB, 6 TP, and 8 PP persons. Interventions: One forearm and calf were treated topically with lidocaine 2.5%/prilocaine 2.5% while contralateral limb served as a control. Laser doppler flowmeters were applied over treated and control sites during limb dependency, cuff inflation and local skin heating (Tloc) up to 42°C. Outcome measures: Skin vascular resistance (SkVR) change with cuff inflation and limb dependency and maximal cutaneous vascular conductance (CVC) during local heating. Results: Change in SkVR was not significantly different between groups or extremity (upper vs. lower) during cuff inflation or limb dependency. However, CVC at Tloc 42°C was significantly different in the lower extremity (LE) of TP and PP (P = 0.007, 0.35) compared to AB. Conclusion: Increases in SkVR during cuff inflation (VAR) and limb dependency (VAR and MYO) are unaltered after SCI, however maximal vasodilation in the LE post-SCI is higher than AB persons.